All tide up - Green, John Patrick, 1975-; Dzioba, Wes (New York, NY : First Second, 2023)
"When a cruise captain is found drifting at sea and delirious, the search begins for his missing ship and passengers! Did it sink? Was it boat-napped? Are supernatural forces at play? And can the InvestiGators unravel this maritime mystery before a second cruise befalls a similarly unfathomable fate? Seas the day and find out in this new nautical adventure!"--
Accelerated Reader AR
Keywords: Private investigators -- Comic books, strips, etc; Alligators -- Comic books, strips, etc; Ocean liners -- Comic books, strips, etc; Pirates -- Comic books, strips, etc; Ship captains -- Comic books, strips, etc; Graphic novels